Drug-susceptible tuberculosis treatment success and associated factors in Ethiopia from 2005 to 2017: a systematic review and meta-analysis - Seid, Mohammed Assen; Ayalew, Mohammed Biset; Muche, Esileman Abdela; Gebreyohannes, Eyob Alemayehu; Abegaz, Tadesse Melaku (BMJ open, 2018)
ObjectivesThe main aim of this study was to assess the overall tuberculosis (TB) treatment success in Ethiopia and to identify potential factors for poor TB treatment outcome.DesignA systematic review and meta-analysis of published literature was conducted. Original studies were identified through a computerised systematic search using PubMed, Google Scholar and Science Direct databases. Heterogeneity across studies was assessed using Cochran’s Q test and I2 statistic. Pooled estimates of treatment success were computed using the random-effects model with 95% CI using Stata V.14 software.ResultsA total of 230 articles were identified in the systematic search. Of these 34 observational studies were eligible for systematic review and meta-analysis. It was found that 117 750 patients reported treatment outcomes. Treatment outcomes were assessed by World Health Organization (WHO) standard definitions of TB treatment outcome. The overall pooled TB treatment success rate in Ethiopia was 86% (with 95% CI 83%_88%). TB treatment success rate for each region showed that, Addis Ababa (93%), Oromia (84%), Amhara (86%), Southern Nations (83%), Tigray (85%) and Afar (86%). Mainly old age, HIV co-infection, retreatment cases and rural residence were the most frequently identified factors associated with poor TB treatment outcome.ConclusionThe result of this study revealed that the overall TB treatment success rate in Ethiopia was below the threshold suggested by WHO (90%). There was also a discrepancy in TB treatment success rate among different regions of Ethiopia. In addition to these, HIV co-infection, older age, retreatment cases and rural residence were associated with poor treatment outcome. In order to further improve the treatment success rate, it is strategic to give special consideration for regions which had low TB treatment success and patients with TB with HIV co-infection, older age, rural residence and retreatment cases.